Strengthening Forest Fire Management in India - Ministry of Environment, Forest and Climate Change, Government of India; World Bank (World Bank, Washington, DC, 2018)
Fire has been a part of India’s landscape since time immemorial and can play a vital role in healthy forests, recycling nutrients, helping tree species regenerate, removing invasive weeds and pathogens, and maintaining habitat for some wildlife. Occasional fires can also keep down fuel loads that feed larger, more destructive conflagrations, but as populations and demands on forest resources have grown, the cycle of fire has spun out of balance. Large areas of degraded forest are now subject to burning on an annual or semi-annual basis. As these fires are no longer beneficial to forest health, India is increasingly wrestling with how to improve the prevention and management of unwanted forest fires. India is not alone in facing this challenge. Forest fires have become an issue of global concern. In many other countries, wildfires are burning larger areas, and fire seasons are growing longer due to a warming climate (Jolly et al 2015). With growing populations in and around the edges of forests, more lives and property is now at risk from fire. About 670,000 k